Dynamics of gas bubbles under acoustic excitation - I.A. Aganin; A.I. Davletshin (Учёные записки Казанского университета: Серия Физико-математические науки)
The dynamics of two gas (air) bubbles in liquid (water) under the action of an ultrasonic traveling wave has been considered. The wave propagates along the straight passing through the bubble centers. The dependencies of the dynamics of the bubbles on the distance between them, their total gas mass, and wave amplitude have been studied for different bubble size ratios under a fixed total gas mass. A mathematical model taking into account the small nonsphericity of the bubbles, liquid viscosity, and compressibility has been used. Three bubble interaction scenarios have been shown to arise: collision of the bubbles, their divergence, and destruction of one of them due to its large deformations. The ranges of the wave amplitude, distance between the bubbles, ratio of their sizes, and value of the total mass of the gas contained in the bubble in which those scenarios are realized have been determined.